Paralog dependency indirectly affects the robustness of human cells. Issue 9 (24th September 2019) - Dandage, Rohan; Landry, Christian R
Abstract: The protective redundancy of paralogous genes partly relies on the fact that they carry their functions independently. However, a significant fraction of paralogous proteins may form functionally dependent pairs, for instance, through heteromerization. As a consequence, one could expect these heteromeric paralogs to be less protective against deleterious mutations. To test this hypothesis, we examined the robustness landscape of gene loss‐of‐function by CRISPR‐Cas9 in more than 450 human cell lines. This landscape shows regions of greater deleteriousness to gene inactivation as a function of key paralog properties. Heteromeric paralogs are more likely to occupy such regions owing to their high expression and large number of protein–protein interaction partners. Further investigation revealed that heteromers may also be under stricter dosage balance, which may also contribute to the higher deleteriousness upon gene inactivation. Finally, we suggest that physical dependency may contribute to the deleteriousness upon loss‐of‐function as revealed by the correlation between the strength of interactions between paralogs and their higher deleteriousness upon loss of function. Synopsis: Meta‐analysis of genome‐wide loss of function screens in human cell lines reveals that deleteriousness of heteromeric paralogs can be largely explained by their inter‐dependency and the unique features of paralog gene expression. Not all paralogs provide robustness to gene inactivation. Interacting paralogs are more deleterious upon gene inactivation. The deleteriousness of the heteromeric interacting paralogs is caused by paralog dependency in an indirect manner. Abstract : Meta‐analysis of genome‐wide loss of function screens in human cell lines reveals that deleteriousness of heteromeric paralogs can be largely explained by their inter‐dependency and the unique features of paralog gene expression.